2015
DOI: 10.1038/srep14584
|View full text |Cite
|
Sign up to set email alerts
|

Illusory Tactile Motion Perception: An Analog of the Visual Filehne Illusion

Abstract: We continually move our body and our eyes when exploring the world, causing our sensory surfaces, the skin and the retina, to move relative to external objects. In order to estimate object motion consistently, an ideal observer would transform estimates of motion acquired from the sensory surface into fixed, world-centered estimates, by taking the motion of the sensor into account. This ability is referred to as spatial constancy. Human vision does not follow this rule strictly and is therefore subject to perc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 31 publications
2
32
0
Order By: Relevance
“…With these parameters, statistical power of the GLMM would be above 80%. This sample size is in accordance with the one reported in similar studies in the literature [7,1,25].…”
Section: Power Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…With these parameters, statistical power of the GLMM would be above 80%. This sample size is in accordance with the one reported in similar studies in the literature [7,1,25].…”
Section: Power Analysissupporting
confidence: 91%
“…Alike in vision, where an observer is able to perceive the depth of a painting in absence of binocular cues, tactile system can encode and process surface motion also when the stimulus lacks one of the redundant motion cues. For instance, a moving pattern generated by a wave of vibrating pins provide a vivid sensation of a moving surface, even in absence of a net shear force [25,10]. On the other hand, the results of the current study showed that deformation cues alone provide sufficient information to discriminate surface speed.…”
Section: Discussionmentioning
confidence: 46%
“…They accounted for the perceived slowing by appealing to the idea that hearing shares the same or a similar slow-motion prior to vision. This idea has been extended to account for a tactile version of the Filehne illusion ( Moscatelli, Hayward, Wexler, & Ernst, 2015 ). The fact that vision, audition, and touch produce similar perceptual errors suggests there may be a common underlying mechanism such as that described by the Bayesian framework.…”
Section: Discussionmentioning
confidence: 99%
“…Our brain fuses these signals to produce a unique and coherent representation of the hands position, contact orientation and motion. Accordingly, in [158] the authors showed that the perception of motion of a touched surface arises from the integration of tactile cues, proprioceptive cues, and prior assumptions on surface motion state.…”
Section: Hand Synergies: Sensingmentioning
confidence: 99%